2003
DOI: 10.1088/0031-9155/48/18/308
|View full text |Cite
|
Sign up to set email alerts
|

Helical cardiac cone beam reconstruction using retrospective ECG gating

Abstract: In modern computer tomography (CT) systems, the fast rotating gantry and the increased detector width enable 3D imaging of the heart. Cardiac volume CT has a high potential for non-invasive coronary angiography with high spatial resolution and short scan time. Due to the increased detector width, true cone beam reconstruction methods are needed instead of adapted 2D reconstruction schemes. In this paper, the extended cardiac reconstruction method is introduced. It integrates the idea of retrospectively gated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 16 publications
0
95
0
1
Order By: Relevance
“…A recent paper [20] has shown that image quality in multi-detector row cardiac CT strongly depends on the choice of the appropriate reconstruction parameters, such as the reconstruction algorithm, reconstruction technique and placement of the reconstruction interval. In our study, the reconstruction technique [21,22] corrects for the cone beam geometry by performing a full 3D filtered back projection which is synchronized with each patient's ECG curve and heart rate by the use of an adaptative multi-segmental reconstruction.…”
Section: Feasibilitymentioning
confidence: 99%
“…A recent paper [20] has shown that image quality in multi-detector row cardiac CT strongly depends on the choice of the appropriate reconstruction parameters, such as the reconstruction algorithm, reconstruction technique and placement of the reconstruction interval. In our study, the reconstruction technique [21,22] corrects for the cone beam geometry by performing a full 3D filtered back projection which is synchronized with each patient's ECG curve and heart rate by the use of an adaptative multi-segmental reconstruction.…”
Section: Feasibilitymentioning
confidence: 99%
“…12 Using specific modifications to conventional MRI pulse sequences, it is also possible to generate and extract a signal that varies in synchrony with the cardiac cycle for later reconstruction. [13][14][15][16] For CT, various methods have been developed, either to recover an imaged volume of the heart in a defined motion state at a single time point 17 or for 4D imaging, by tracking the projection's center of mass. 18 ECG-free algorithms have also been used for US imaging.…”
Section: Introductionmentioning
confidence: 99%
“…f a(t) + l ζ dl, (1) where ζ ∈ S 2 is a unit vector in R 3 (S 2 is the unit sphere in R 3 ), a(t) ∈ R 3 is the x-ray source position at time t ∈ T ⊂ R, t is then also the source trajectory parameter in R 3 , see Fig. 1.…”
Section: A 3d Cone Beam Notationsmentioning
confidence: 99%
“…The problem under consideration is the reconstruction of f , or equivalently of f Γ t , from cone-beam measurements Df Γt , see (1), for known deformation functions Γ t , t ∈ T . Our objective is to apply efficient accurate deformation corrections in the reconstruction algorithms.…”
Section: B Deformation Modelmentioning
confidence: 99%
See 1 more Smart Citation